The Factors that Affect the Selecting of Sticker Image on Social Media Application: A Case Study of Retired People Purchasing Behavior in Thailand - Satcharoen, Kleddao; Tangtisanon, Pikulkaew (My University, 2022)
This research aimed to investigate factors that influence retirees in Thailand on selection of Line stickers image to purchase. The study uses an integrated model of attitude-behavior decision-making, incorporating the theory of planned behavior (TPB) and technology acceptance model (TAM) along with personal and demographic factors. The data were collected via online questionnaire survey, from 400 retirees who live in Thailand. The results showed that an integrated model that incorporated TPB and TAM was generally successful at predicting consumer attitudes, behavioral intentions, and behaviors toward the purchase of Line stickers image. However, there was a notable exception, which was that subjective norms did not have a significant effect on attitudes except for perceived ease of use.
Keywords: line stickers image; purchase behavior; retired people; selecting behavior; selection; social media sticker